POJOK EDUKASI DIGITAL PADA AREA PERMAINAN ANAK TRIPLE KIDS - IGKG Puritan Wijaya ADH; , I Gede Putra Mas Yusadara; Ni Putu Putri Ayu Wijayanthi; arya, I Made Arya Budhi Saputra; I Made Bhaskara Gautama; I Nyoman Sutya Alit Swadarma; I Putu Aditya Sastra Wirawan (Universitas PGRI Yogyakarta, 2025)
Triple Kids is a Playground service provider in the Lumintang area of ​​North Denpasar which has been operating since 2020 with many visitors to the community in the Lumintang area. With the level of crowds and interest of visitors in utilizing the indoor play area facilities, UKM Triple Kids has problems in managing the number of children's visitors at any given time, especially when there are lots of visitors. The management is unable to control the time of children's visitors if it has passed the specified time limit, so assistance is needed in managing entrance tickets and limiting the time for visitors to play in the play area, including managing financial administration and regular visitor members in the Triple Kids play area. With these busy conditions, it is necessary to provide a play area with the help of digital technology which can also help children's interest in playing but can still train children's motoric activities, practice socialization and interaction. Therefore, the Management of Triple Kids welcomes it by conveying the need for digital education facilities that can still improve children's motor skills. Keywords: Playground, Children, Tickets